Peningkatan Kesadaran Masyarakat dalam Pengelolaan Sampah Plastik Terpadu di Nagari Batu Basa - Syaiful Haq; Hendra Hidayat; Dori Yuvenda; Ryan Fikri; Rizky Indra Utama; Rizal Kurniawan; Anggarda Muji (CV. ITTC INDONESIA, 2026)
Environmental problems caused by suboptimal waste management have become a major issue in Nagari Batu Basa, particularly the habit of residents disposing of waste into rivers. This condition worsens during the dry season, as waste accumulation generates unpleasant odors and poses health risks, especially from plastic waste that is difficult to decompose and has even contributed to malaria cases among some community members. This community service activity aims to increase public awareness of integrated plastic waste management and to discourage residents from disposing of waste into rivers. The methods employed consist of four approaches. The first approach involves the provision of educational waste posts as an initial effort to prevent indiscriminate waste disposal. The second approach is the construction of an integrated plastic waste collection facility at the nagari office, equipped with dry waste sorting facilities. In addition, the community was provided with training on ecobrick production, which could be exchanged for incentives. The fourth approach applies a door-to-door collection method through the involvement of KKN students from Universitas Negeri Padang (UNP), who collected waste that had been gathered by the community from shops, schools, and mosques. The results of the community service activities indicate positive community engagement, as evidenced by the successful production of 300 ecobricks by the community in collaboration with KKN UNP students, of which 260 were branded as Nagari Batu Basa ecobricks. This activity contributes significantly to building community awareness of household-level waste segregation and supports the creation of a healthier and more sustainable nagari environment.